Methotrexate‐associated lymphoproliferative disorder with an osteolytic vertebral lesion in an elderly patient with rheumatoid arthritis: A case report. (25th March 2021) - Hirata, Chihiro; Kenzaka, Tsuneaki; Akita, Hozuka
Abstract: What is known and objective: Methotrexate‐associated lymphoproliferative disorder (MTX‐LPD) is a rare complication that develops in patients treated with methotrexate (MTX). Case summary: A 76‐year‐old male patient had been taking MTX for his rheumatoid arthritis. Computed tomography (CT) revealed masses in the liver, right adrenal gland and T6‐T7 vertebra, including an osteolytic lesion. FDG‐PET scan showed increased uptake in each lesion. MTX was discontinued, and CT showed complete remission of the tumours after three months. The disease course confirmed MTX‐LPD diagnosis. What is new and Conclusion: Bone lesions in LPDs mimic those of metastatic cancer. MTX‐LPD should be considered in patients on MTX presenting with mass lesions. Abstract : Bone lesions in LPDs mimic those of metastatic cancer. MTX‐LPD should be considered in patients on MTX presenting with mass lesions.